1988
DOI: 10.1016/0014-5793(88)80811-1
|View full text |Cite
|
Sign up to set email alerts
|

The fluorescence intensity of the lipophilic probe N‐phenyl‐1‐naphthylamine responds to the oxidation‐reduction state of purified Escherichia coli cytochrome o incorporated into phospholipid vesicles

Abstract: N-Phenyl-l-naphthylamine (NPN), a reagent which has been used previously to probe the fluidity or microviscosity of the membrane lipids of intact cells of Escherichia coli, was found to respond to the redox state of purified eytochrome o incorporated into lipid vesicles formed from purified or E. coli phospholipids. NPN was bound to the proteoliposomes to produce a steady-state level of fluorescence intensity. Addition of the substrate ascorbate, in the presence of phenazine methosulfate as an electron donor, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…NPN is a fluorescent probe with moderate hydrophobicity, which was frequently used in biology for measurements of membrane permeability induced by different biological events and also in the characterization of the aggregates formed by surfactants or amphiphilic polymers . Its known ability to change the emission intensity maximum and to undergo a batochromic shift of this maximum with decreasing polarity and increasing viscosity of the environment was used for the characterization of amphiphile aggregates.…”
Section: Resultsmentioning
confidence: 99%
“…NPN is a fluorescent probe with moderate hydrophobicity, which was frequently used in biology for measurements of membrane permeability induced by different biological events and also in the characterization of the aggregates formed by surfactants or amphiphilic polymers . Its known ability to change the emission intensity maximum and to undergo a batochromic shift of this maximum with decreasing polarity and increasing viscosity of the environment was used for the characterization of amphiphile aggregates.…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesize that the contribution of pigment may play varied roles in different strains since our NPN test showed that the permeability of the outer cell membrane was distinct between ES191 and AGRFS2961 ( Figure 2 ). Edward et al [ 21 ] demonstrated that the efficiency of NPN binding to phospholipids was influenced by the redox state of cytochrome o incorporated into phospholipid vesicles in E. coli. The addition of H 2 O 2 resulted in the immediate reoxidation of cytochrome o and loss of the NPN fluorescence increase observed [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Edward et al [ 21 ] demonstrated that the efficiency of NPN binding to phospholipids was influenced by the redox state of cytochrome o incorporated into phospholipid vesicles in E. coli. The addition of H 2 O 2 resulted in the immediate reoxidation of cytochrome o and loss of the NPN fluorescence increase observed [ 21 ]. We hypothesize that blue-LED induced ROS, particular H 2 O 2 (the focus in our study), possibly inhibited NPN uptake in a strain-dependent manner, as evidenced by constant cell permeability in AGRFS2961/BAA894 strain whereas ES191 had a significant change on the cell permeability, resulting in a differentiated light-susceptible phenotype.…”
Section: Discussionmentioning
confidence: 99%